Análise de energia incidente em redes de distribuição: estimação, estratégias de mitigação e medidas de proteção - Camponogara, Marina (2021)
An electric arc occurs when the air’s ionization is sufficient to allow the passage of electric current and arises from two or more conductors separated by a given spacing subjected to a short-circuit, either by improper contact or insulation failure, or even during the routine operation of electrical equipment, such as in the process of opening and closing maneuvering devices. A series of risks are associated to electric arc, the thermal risk being accepted as the most significant, as accidents documented as caused by this type of phenomenon are predominantly burns. Large amounts of energy are released during the occurrence of an electric arc, the thermal energy being called incident energy. Within the arc flash risk assessment process, the incident energy analysis is employed to predict the incident energy levels generated in a possible arc flash event and, as result of this analysis, it is possible to determine the appropriate protective equipment for the work in that site, whether there is the need to employ incident energy mitigation techniques, and whether the work can actually be carried out in an energized location or whether it will be necessary for the point to be de-energized. In this work, an incident energy analysis is proposed for distribution grids, in which incident energy levels must be estimated, mitigation techniques proposed when necessary, and worker protection measures determined. The employed grids in the case studies are the IEEE 13-Node and IEEE 34-Bus grids, as they have points within the voltage range of the selected incident energy estimation guide, the IEEE Std 1584. Both 2002 and 2018 models are used to obtain a comparison among the results. The ATPDraw software is used to simulate bolted three-phase faults at the points of interest and the clothing and other pertinent protective equipment are chosen from NFPA 70E-2021. The results of the case studies confirm the direct relation between the incident energy and the arc duration, in addition to highlighting the difference among the results obtained using the 2002 and 2018 models as more expressive for scenarios with horizontally oriented conductors and in low voltage systems, mainly due to the arc current variation factor. For medium voltage systems, the spacing range considered in the IEEE Std 1584-2002’s empirical model is different from the IEEE Std 1584-2018 model, forcing the use of the theoretical model, based on the Lee model, which implies in more conservative results. Finally, considering the voltage ranges of both models, there is a limitation regarding their application in distribution systems, as they do not include all voltages used in medium and high voltage grids.